Factors associated with decision making on COVID-19 vaccine acceptance among college students in South Carolina. Issue 1 (2nd January 2022) - Tam, Cheuk Chi; Qiao, Shan; Li, Xiaoming
ABSTRACT: COVID-19 vaccination could be a promising approach in controlling the pandemic, but its success relies on the vaccine acceptance among various populations including young adults who are vulnerable to COVID-19 due to active lifestyle and perceived invulnerability. Vaccine acceptance decisions can be influenced by multiple factors and people may weigh these factors differently in decision making. The current study aimed to explore COVID-19 vaccine acceptance among college students in South Carolina and examine how they weigh these factors according to their COVID-19 vaccine acceptance levels (i.e. acceptance, hesitance, refusal). Online survey data were collected from 1062 college students in South Carolina between September and October 2020. Multinomial logistic regresssion was used to compare perceived importance of 12 factors affecting levels of vaccine acceptance, controlling for demographic variables. About 26.1% of participants reported they would definitely take COVID-19 vaccines when available. Compared to acceptance group, refusal and hesitance groups considered side effects and vaccine characteristics (e.g. where the vaccine is produced) as important. Hesitance group considered authoritative advice from school/college as important. Acceptance group considered authoritative advice from government/doctors and local availability of the vaccines and local availability of the vaccines as important. Our findings suggest relatively low vaccine acceptance among college students in South Carolina and different factors were considered in their vaccination decision according to their acceptance levels. Tailored vaccine promotion messages should address specific concerns among the refusal and hesitancy groups. Schools should attend to valid communication strategies in vaccine campaign since the hesitancy group considered school's advice as important. College health educators also need to pay attention to the refusal group who do not value duration of protection or authoritative advice as much as their counterparts in vaccine decision making.